Chronic Rhinosinusitis with Polyps Is Characterized by Increased Mucosal and Blood Th17 Effector Cytokine Producing Cells - Miljkovic, Dijana; Psaltis, Alkis J.; Wormald, Peter J.; Vreugde, Sarah (Frontiers in Physiology, 2017)
Background Recent studies have implied a role for Th17 cells in CRS with nasal polyps (CRSwNP) patients. However, the capacity of these cells to produce Th17 cytokines is still unknown. Here we sought to quantify IL-17A, IL17-F, IL-21 and IL-22 cytokines produced by Th17 cells in mucosal tissue and peripheral blood of CRSwNP, CRS without nasal polyps (CRSsNP) and control patients. Methods Samples were prospectively collected from CRS patients and non-CRS controls. We used flow cytometry to characterise the Th17 cells and their cytokines in sinonasal tissue and peripheral blood. Results A total of 36 patients were recruited to the study. CRSwNP patients had significantly more tissue IL-17A (9.53 +/- 2.71 vs 1.11 +/ -0.43 vs 0.77 +/- 0.07), IL-17F (4.96 +/- 1.48 vs 0.88 +/-0.31 vs 0.56 +/- 0.04), IL-21 (5.55 +/- 2.01 vs 1.60 +/- 0.71 vs 1.53 +/- 0.55) and IL-22 (4.73 +/- 1.58 vs 0.70+/-0.28 vs 0.88 +/- 0.26) producing Th17 cells compared to CRSsNP and control mucosa per mg of tissue respectively. Allergic CRSwNP patients had decreased numbers of IL-21 producing Th17 cells compared to non-Allergic CRSwNP. (1.69 +/- 0.57 vs 9.41+/-3.23) per mg of tissue respectively (Kruskal-Wallis p<0.05). Conclusion In summary our study identified increased amounts of Th17 derived cytokines IL-17A, IL-17F, IL21 and IL22 in CRSwNP patient polyps and peripheral blood suggesting a local and systemic role for Th17 cells in CRS. Atopic CRSwNP had decreased amounts of tissue Th17 cell derived IL-21 implying a potential protective role for IL-21 in CRSwNP allergic inflammation.